Safety and Feasibility of Repeated Intrathecal Allogeneic Bone Marrow-Derived Mesenchymal Stromal Cells in Patients with Neurological Diseases - Kuang Pan; Lingna Deng; Peiying Chen; Qingxia Peng; Jingrui Pan; Yanfeng Wu; Yidong Wang (Stem Cells International)
Mesenchymal stromal cells (MSCs) have become the most commonly used adult stem cells in regenerative medicine. Preclinical studies have shown that MSCs-based therapy is a potential new treatment approach for neurological diseases. Intrathecal injection has unique feature which allows stem cells to directly migrate to the lesion site in patients with central nervous system (CNS) diseases. In this study, we evaluate the safety and feasibility of intrathecal allogeneic bone marrow-derived MSCs (BM-MSCs) in patients with neurological diseases. This open-label clinical study included 37 patients (14 diseases). Eligible patients underwent a baseline assessment and were intrathecally injected with allogeneic BM-MSCs (1×106 cells/kg, 4 consecutive treatments at 1-week intervals). After four infusions, the patients were followed up for at least 6 months. Adverse events, cerebrospinal fluid (CSF) test results, clinical symptoms, physical examination, and haematological and imaging examinations were used to assess the safety and feasibility of the treatment. Also, we performed a systematic review of the safety of all types of intrathecal stem cells and compared our result to previous studies. In our study, the highest adverse event was a slight ache at the injection site (4.11%), followed by fever (3.42%) and mild headache (2.05%). No severe adverse events were reported. After the intrathecal injections, the white blood cell (WBC) counts in the CSF increased in 30 patients and the protein concentration in the CSF exceeded the normal range in 26 patients, while other CSF indicators remained normal. Moreover, these patients had no suspected manifestations of CNS infection. Haematological and imaging examinations showed no abnormal changes after BM-MSCs infusion. Compared with previous studies, the incidence of adverse events was nearly consistent or even lower for headache, fever, nausea, and neck pain. In conclusion, repeated intrathecal allogeneic BM-MSCs are safe, feasible, and promising for the treatment of patients with neurological diseases.